Origin activation requires both replicative and accessory helicases during T4 infection - Brister, J. Rodney (2008)
SUMMARY: The bacteriophage T4 has served as an in vitro model for the study of DNA replication for several decades, yet less is known about this process during infection. Recent work has shown that viral DNA synthesis is initiated from at least five origins of replication distributed across the 172 kb chromosome, but continued synthesis is dependent on recombination. Two proteins are predicted to facilitate loading of the hexameric 41 helicase at the origins, the Dda accessory helicase and the 59 loading protein. Using a real time, genome-wide assay to monitor replication during infections, it is shown here that dda mutant viruses no longer preferentially initiate synthesis near the origins, implying that the Dda accessory helicase has a fundamental role in origin selection and activation. In contrast, at least two origins function efficiently without 59 loading protein, indicating that other factors load 41 helicase at these loci. Hence, normal T4 replication includes two mechanistically distinct classes of origins, one requiring 59 helicase loader, and a second that does not. Since both mechanisms require an additional factor, repEB, for sustained activation, normal T4 origin function appears to include at least three common elements, origin selection and initial activation, replisome loading, and persistence.